Bipolar current collector, preparation method thereof, battery and application

By introducing a nickel-chromium alloy transition layer into the repolar current collector of the bipolar battery, the problem of unstable interface of the copper-aluminum composite current collector is solved, and the cycling performance of the battery is significantly improved.

CN119517991AActive Publication Date: 2025-02-25JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD

Patent Information

Application Number
CN202411697289.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The interface of the copper-aluminum composite fluid collection in bipolar batteries is unstable, resulting in attenuation of the battery cycle performance.

Method used

The transition layer of nickel-chromium alloy is introduced into the repolar current collector, and the crystallinity is defined to be 5-80% to improve the adhesion between the negative electrode conductive layer and the positive electrode conductive layer.

Benefits of technology

It improves the stability of the interface, ensures the structural stability of the repolar current collector, and promotes the cycling performance of the bipolar battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005154026580000171
    Figure BDA0005154026580000171
  • Figure BDA0005154026580000181
    Figure BDA0005154026580000181
  • Figure BDA0005154026580000192
    Figure BDA0005154026580000192
Patent Text Reader

Abstract

The invention provides a bipolar current collector and a preparation method thereof, a battery and application, the bipolar current collector comprises a negative electrode conductive layer and a positive electrode conductive layer which are laminated, and at least one transition layer is laminated between the negative electrode conductive layer and the positive electrode conductive layer; the transition layer is made of nickel-chromium alloy, the crystallinity of the nickel-chromium alloy is 5-80%, and the transition layer is of a nonporous structure. Starting from the material and structural design of the bipolar current collector, the nonporous transition layer made of the nichrome is added, and meanwhile, the crystallinity of the nichrome is limited to be 5-80%, so that the bonding force between the negative conductive layer and the positive conductive layer can be improved, and the stability of an interface is improved; the bipolar current collector is ensured to have good structural stability, the application stability of the bipolar current collector in a battery can be promoted, and the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a bipolar current collector and a preparation method thereof, a battery and applications. Background Art

[0002] At present, with the continuous penetration of electric vehicles, the market has put forward higher requirements for the endurance of electric vehicles. In order to solve the endurance problem of electric vehicles, it is imperative to develop batteries with high specific energy. Among many solutions, bipolar batteries continue to attract people's attention as high specific energy batteries with good prospects. Bipolar batteries are batteries in which bipolar pole pieces (pole pieces prepared by coating positive and negative electrode materials on both sides of the current collector) are stacked in series. Due to the series conduction of its own current collector, the wires between the electrodes in traditional batteries are eliminated, thereby reducing the mass and volume of the battery, improving the battery energy density, and its series battery structure can increase the output voltage and power of the battery, thereby increasing the output power of the battery. It is reported that with bipolar batteries, the number of cells that can be accommodated in a battery pack of the same size is equivalent to 1.4 times that of a traditional battery, and the output power of the battery is about 1.5 times that of a traditional battery, showing good potential.

[0003] As an important component of bipolar batteries, the bipolar current collector has a great influence on the battery's structural stability. At present, copper-aluminum composite current collectors are usually used. However, the bonding force between the copper layer and the aluminum layer in the copper-aluminum composite current collector is poor, resulting in an unstable interface between the two, which is easy to delaminate during battery processing and use, causing an increase in interface resistance, thereby causing the cycle performance of the prepared bipolar battery to decay.

[0004] Therefore, how to effectively improve the bonding force between the negative electrode conductive layer and the positive electrode conductive layer in the bipolar current collector, improve the interface stability, and then improve the cycle performance of the bipolar battery is a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the deficiencies of the prior art, the object of the present invention is to provide a bipolar current collector and a preparation method thereof, a battery and an application thereof. Starting from the material and structural design of the bipolar current collector, the present invention adds a transition layer made of a nickel-chromium alloy, and limits the crystallinity of the nickel-chromium alloy to 5-80%. This design can not only improve the bonding force between the negative electrode conductive layer and the positive electrode conductive layer, thereby improving the stability of the interface and ensuring that the bipolar current collector has good structural stability, but also promote the application stability of the bipolar current collector in the battery and improve the cycle performance of the battery.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a bipolar current collector, comprising a negative electrode conductive layer and a positive electrode conductive layer stacked together, wherein at least one transition layer is stacked between the negative electrode conductive layer and the positive electrode conductive layer.

[0008] The material of the transition layer includes nickel-chromium alloy, and the crystallinity of the nickel-chromium alloy is 5-80%.

[0009] Starting from the material and structural design of the bipolar current collector, the present invention adds a transition layer made of nickel-chromium alloy, and at the same time limits the crystallinity of the nickel-chromium alloy to 5-80%. This design can not only improve the bonding force between the negative electrode conductive layer and the positive electrode conductive layer, thereby improving the stability of the interface and ensuring that the bipolar current collector has good structural stability, but also promote the application stability of the bipolar current collector in the bipolar battery and improve the cycle performance of the bipolar battery.

[0010] In the present invention, the nickel-chromium alloy has a variety of excellent properties, including good mechanical properties (such as high strength, high toughness and wear resistance), corrosion resistance, heat resistance, electrical conductivity and plasticity.

[0011] In the present invention, the crystallinity of the nickel-chromium alloy is 5-80%, for example, it can be 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70% or 80%, etc., preferably 20-60%. If the crystallinity of the nickel-chromium alloy is too low, the corrosion resistance of the electrolyte is poor; if the crystallinity of the nickel-chromium alloy is too high, the transition layer is brittle and is prone to breakage during the rolling process of the prepared pole piece, resulting in defects, resulting in poor material stability and poor battery cycle performance.

[0012] Preferably, the transition layer is a non-porous structure.

[0013] In the present invention, the transition layer is a non-porous structure. If there are holes in the nickel-chromium alloy, the interface is easily corroded by the electrolyte, resulting in poor interface stability, which leads to a decrease in the capacity retention rate during the battery cycle. When there are hole defects in the positive and negative conductive layers adjacent to the nickel-chromium alloy layer, due to the lack of the barrier effect of the interface layer, the electrolyte is likely to flow between the positive and negative conductive layers adjacent to the nickel-chromium alloy layer, causing a battery short circuit. In addition, the non-porous structure can ensure more beneficial mechanical properties (such as tensile strength and elongation at break) and battery capacity retention rate.

[0014] It should be noted that the bipolar current collector refers to the bipolar current collector.

[0015] Preferably, in the nickel-chromium alloy, the mass proportion of nickel is 10-90%, for example, it can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90%.

[0016] In the present invention, the appropriate nickel mass ratio helps the transition layer to achieve good composite with the positive and negative electrode conductive layers. If the nickel mass ratio is too low, it is not conducive to improving the interface stability between the negative electrode conductive layer and the positive electrode conductive layer, thereby causing the battery's cycle performance to deteriorate; if the nickel mass ratio is too high, it is not conducive to improving the interface stability between the negative electrode conductive layer and the positive electrode conductive layer, causing the assembled battery's cycle performance to deteriorate.

[0017] Preferably, the single layer thickness of the transition layer is 5-100 nm, for example, it can be 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, etc., preferably 10-100 nm.

[0018] In the present invention, the thickness of the appropriate single-layer transition layer can better improve the bonding force between the negative electrode conductive layer and the positive electrode conductive layer. If the single-layer thickness of the transition layer is too small, the bonding force between the negative electrode conductive layer and the positive electrode conductive layer cannot be effectively improved, and it is easy to break during the rolling process of the prepared pole piece, resulting in defects, resulting in poor material stability and poor battery cycle performance; if the single-layer thickness of the transition layer is too large, the bonding force between the negative electrode conductive layer and the positive electrode conductive layer cannot be further improved, and the material cost is increased, and the battery cycle performance is poor.

[0019] In the present invention, when the transition layer satisfies the relationship between crystallinity and thickness at the same time, the following problems existing when the crystallinity between the conductive layer and the transition layer does not match can be effectively avoided:

[0020] (1) Stress concentration is likely to occur at the interface, which in turn leads to cracks at the interface, thereby weakening the mechanical strength of the overall structure.

[0021] (2) Poor adhesion at the interface, resulting in delamination during use.

[0022] When the transition layer satisfies the relationship between crystallinity and thickness at the same time, it is possible to achieve improvements in technical effects such as adhesion, stability, and mechanical properties without considering the crystallinity matching between the transition layer and the conductive layer, greatly reducing the difficulty of controlling the production process.

[0023] Preferably, at least two transition layers are stacked between the negative electrode conductive layer and the positive electrode conductive layer, and the mass content of nickel in the at least two transition layers increases gradually in a direction away from the negative electrode conductive layer or the positive electrode conductive layer.

[0024] In the present invention, the design of the multi-layer transition layer is coordinated with the gradient change of the mass content of nickel, which helps to reduce the interface resistance between the transition layer and the conductive layer and improve the structural stability of the transition layer.

[0025] Preferably, the total thickness of the at least two transition layers is 10-100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm.

[0026] Preferably, the thickness of the negative electrode conductive layer is ≥0.1 μm, for example, it can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc., preferably 1-10 μm.

[0027] In the present invention, considering the cost and the impact on the battery energy density, the thickness of the negative electrode conductive layer is preferably 1-10 μm. If it is too thin, the conductivity is poor; if it is too thick, the surface density of the current collector is too high, resulting in a low energy density of the prepared battery.

[0028] Preferably, the thickness of the positive electrode conductive layer is ≥0.5 μm, for example, it can be 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc., preferably 1-10 μm.

[0029] In the present invention, considering the cost and the impact on the battery energy density, the thickness of the positive electrode conductive layer is preferably 1-10 μm. If it is too thin, the conductivity is poor; if it is too thick, the surface density of the current collector is too high, resulting in a low energy density of the prepared battery.

[0030] Preferably, the total thickness of the negative electrode conductive layer and the positive electrode conductive layer is ≥2 μm, for example, it can be 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm.

[0031] In the present invention, if the total thickness of the negative electrode conductive layer and the positive electrode conductive layer is too low, the mechanical strength and conductivity of the prepared complex electrode current collector are relatively poor, which affects the processing performance of the complex electrode current collector and the cycle performance of the assembled battery.

[0032] Preferably, the material of the negative electrode conductive layer includes any one or a combination of at least two of copper, nickel, titanium, carbon, gold or silver, preferably any one or a combination of at least two of copper, nickel or carbon. Exemplary materials include stainless steel, copper-nickel alloy, nickel-titanium alloy, copper-titanium alloy, gold-silver alloy, etc.

[0033] Preferably, the negative electrode conductive layer further includes doping elements.

[0034] Preferably, the doping element includes any one of tungsten, manganese, iron, chromium, cobalt, zirconium, tantalum, niobium or tin, or a combination of at least two of them.

[0035] Preferably, the mass fraction of the doping element in the negative electrode conductive layer is 0.01-10%, for example, it can be 0.01%, 0.1%, 1%, 5% or 10%.

[0036] The present invention dopes the negative electrode conductive layer with the above-mentioned doping elements to improve its mechanical properties and corrosion resistance, but the content should not be too high, as too high a content will lead to poor conductivity of the prepared bipolar current collector, while too low a content will have no effect.

[0037] Preferably, the material of the positive electrode conductive layer includes any one of aluminum, carbon, gold or silver, or a combination of at least two thereof, preferably aluminum and / or carbon, for example, aluminum-gold alloy, gold-silver alloy or silver-aluminum alloy.

[0038] Preferably, a protective layer is provided on the surface of the negative electrode conductive layer and / or the positive electrode conductive layer away from the transition layer.

[0039] In the present invention, the protection layer is designed to prevent the negative electrode conductive layer from being oxidized.

[0040] Preferably, the thickness of the protective layer is 5-100 nm, for example, it can be 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, etc., preferably 10-80 nm.

[0041] Preferably, the material of the protective layer includes any one of a metal element, a carbon material, an alloy or an oxide, or a combination of at least two thereof. Exemplarily, the metal element is nickel or chromium, the carbon material is graphite, carbon black, carbon nano quantum dots, carbon nanotubes, carbon nanofibers or graphene, the alloy is a nickel-based alloy and / or a copper-based alloy, and the oxide is aluminum oxide, silicon oxide, nickel oxide, chromium oxide, cobalt oxide or copper-chromium oxide.

[0042] It should be noted that, when the negative electrode conductive layer is a copper layer, the protective layer is disposed on the surface of the copper layer away from the transition layer.

[0043] Preferably, a protective layer is provided on the surface of the positive electrode conductive layer away from the transition layer, and the thickness of the protective layer is 5-100nm, for example, it can be 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm, etc. The material of the protective layer includes any one of a metal element, a carbon material, an alloy or an oxide, or a combination of at least two of them.

[0044] In a second aspect, the present invention provides a method for preparing the bipolar current collector as described in the first aspect, the preparation method comprising the following steps:

[0045] A positive electrode conductive layer is provided, and then at least one transition layer and a negative electrode conductive layer are compounded in sequence on one side surface of the positive electrode conductive layer to obtain the bipolar current collector.

[0046] Alternatively, a negative electrode conductive layer is provided, and then at least one transition layer and a positive electrode conductive layer are compounded in sequence on one side surface of the negative electrode conductive layer to obtain the bipolar current collector.

[0047] It should be noted that the positive electrode conductive layer can be made of commercial foil materials, such as aluminum foil.

[0048] Preferably, the composite method of the at least one transition layer comprises at least one method selected from the group consisting of a mechanical rolling method, a bonding method, a vapor deposition method, a chemical plating method and an electroplating method.

[0049] Preferably, the vapor deposition method includes magnetron sputtering and / or vacuum evaporation.

[0050] Preferably, the composite method of the at least one transition layer is magnetron sputtering, and the specific parameters independently include:

[0051] The target material is a nickel-chromium target with a nickel mass content of 10-90% (for example, 10%, 20%, 30%, 40%, 50%, 60%, 70% or 80%, etc.), the power supply is a pulsed DC power supply, the power supply frequency is 5-50kHz, for example, 5kHz, 10kHz, 20kHz, 30kHz, 40kHz or 50kHz, etc., the target power is 2-20kW, for example, 2kW, 5kW, 10kW, 15kW or 20kW, etc., and the gas flow rate is 3 0-500mL / min, for example, it can be 30mL / min, 50mL / min, 100mL / min, 200mL / min, 300mL / min, 400mL / min or 500mL / min, etc., the chamber vacuum degree is ≤0.1Pa, for example, it can be 0.1Pa, 0.05Pa or 0.01Pa, etc., the cooling temperature of the coating main roller is 5-30℃, for example, it can be 5℃, 10℃, 15℃, 20℃, 25℃ or 30℃, etc.

[0052] Preferably, the preparation methods of the positive electrode conductive layer and the negative electrode conductive layer are independently any one of physical vapor deposition, chemical vapor deposition, rolling or coating-drying methods, or a combination of at least two thereof. Exemplarily, the physical vapor deposition method may be magnetron sputtering, etc., and the chemical vapor deposition method may be plasma enhanced chemical vapor deposition, etc.

[0053] It should be noted that when the negative electrode conductive layer or the positive electrode conductive layer is a carbon layer, the coating-drying method is used for deposition.

[0054] Preferably, when the material of the negative electrode conductive layer is copper, a protective layer is provided on the surface of the negative electrode conductive layer away from the transition layer, and the preparation method of the protective layer includes any one of physical vapor deposition, chemical vapor deposition, in-situ forming or coating, or a combination of at least two thereof. It should be noted that the physical vapor deposition method is preferably a vacuum evaporation method or a magnetron sputtering method, the chemical vapor deposition method is preferably a normal pressure chemical vapor deposition method or a plasma enhanced chemical vapor deposition method, the in-situ forming method is preferably a method of forming a protective layer in situ on the surface of the copper layer, and the coating method is preferably a die coating method, a blade coating method or an extrusion coating method, etc.

[0055] In a third aspect, the present invention provides an application of the bipolar current collector as described in the first aspect in the fields of electromagnetic shielding, flexible circuits and printed circuit boards.

[0056] In a fourth aspect, the present invention provides a battery, wherein the pole piece in the battery comprises the multi-electrode current collector as described in the first aspect.

[0057] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] (1) Starting from the material and structural design of the complex current collector, the present invention adds a transition layer made of nickel-chromium alloy, and at the same time limits the crystallinity of the nickel-chromium alloy to 5-80%. This design can not only improve the adhesion between the negative electrode conductive layer and the positive electrode conductive layer, thereby improving the stability of the interface and ensuring that the complex current collector has good structural stability, but also promote the application stability of the complex current collector in the bipolar battery and improve the cycle performance of the battery.

[0060] (2) The preparation method provided by the present invention is simple, easy to operate, and suitable for large-scale promotion. DETAILED DESCRIPTION

[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0062] Example 1

[0063] This embodiment provides a bipolar current collector, which includes a negative electrode protection layer, a negative electrode conductive layer, a transition layer, a positive electrode conductive layer and a positive electrode protection layer that are stacked.

[0064] The material of the transition layer is a nickel-chromium alloy, in which the mass percentage of nickel is 80%; the crystallinity of the nickel-chromium alloy is 51%, and the transition layer is a non-porous structure; the transition layer is a single layer with a thickness of 10 nm.

[0065] The negative electrode protective layer is made of copper chromium oxide with a thickness of 5 nm. The negative electrode conductive layer is made of copper with a thickness of 1 μm. The positive electrode conductive layer is a commercial aluminum foil (commercial aluminum foil has its own aluminum oxide protective layer) with a thickness of 13 μm. The total thickness of the negative electrode conductive layer and the positive electrode conductive layer is 14 μm.

[0066] This embodiment also provides a method for preparing the above-mentioned bipolar current collector, and the preparation method comprises the following steps:

[0067] (1) A commercial aluminum foil is provided as a positive electrode conductive layer, and then the aluminum foil is placed in a magnetron sputtering machine to deposit a transition layer on one side of the aluminum foil. The specific process conditions of the transition layer magnetron sputtering are:

[0068] A nickel-chromium target (purity: 99.99%, nickel mass content of 80%) was used as the target material, a pulsed DC power supply was used, the power frequency was 20 kHz, the target power was 5.0 kW, the argon flow rate was 50 mL / min, the chamber vacuum was 0.08 Pa, the sputtering time was 2 s, and the temperature of the main roller during the deposition process was 15°C.

[0069] (2) placing the composite layer obtained in step (1) in a magnetron sputtering machine to deposit a copper layer on the surface of the transition layer. The specific process conditions are:

[0070] A copper target (purity 99.99%) was used as the target material, the target power was 10 kW, the argon flow rate was 80 mL / min, the chamber pressure was 0.1 Pa, the sputtering time was 130 s, and the main roller cooling temperature was -10°C.

[0071] (3) The composite layer prepared in step (2) is placed in a 0.6 g / L chromic acid aqueous solution for 20 seconds, and then the surface liquid is removed and dried at 70° C. to obtain a negative electrode protective layer, thereby completing the preparation of the bipolar current collector.

[0072] In the present invention, the surface pores of the transition layer can be detected in the following manner:

[0073] Take the finished bipolar current collector, randomly select 5 positions on the bipolar current collector, and use focused ion beam (FIB) to prepare cross-sectional samples to prepare cross-sectional analysis samples that meet the transmission electron microscope (TEM) test requirements (the cross section includes the negative electrode conductive layer, the positive electrode conductive layer and the transition layer). Then use TEM to magnify and observe the transition layer of the cross section. The characterization result shows that there are no holes in the 5 positions, and it is judged that the transition layer has no holes.

[0074] Example 2

[0075] The difference between this embodiment and embodiment 1 is that the mass content of nickel in the nickel-chromium target is 50%, the target power is 5.3 kW, and the mass ratio of nickel to chromium in the nickel-chromium alloy of the transition layer is 50:50.

[0076] The rest of the preparation methods and parameters were the same as those in Example 1.

[0077] Example 3

[0078] The difference between this embodiment and embodiment 1 is that the mass content of nickel in the nickel-chromium target is 10%, the target power is 6.0 kW, and the mass ratio of nickel to chromium in the nickel-chromium alloy of the transition layer is 10:90.

[0079] The rest of the preparation methods and parameters were the same as those in Example 1.

[0080] Example 4

[0081] The difference between this embodiment and embodiment 1 is that the mass content of nickel in the nickel-chromium target is 90%, the target power is 4.7 kW, and the mass ratio of nickel to chromium in the nickel-chromium alloy of the transition layer is 90:10.

[0082] The rest of the preparation methods and parameters were the same as those in Example 1.

[0083] Example 5

[0084] The difference between this embodiment and embodiment 1 is that the sputtering time in the deposition process of the transition layer is adjusted to 1 s, so that the thickness of the transition layer is 5 nm.

[0085] The rest of the preparation methods and parameters were the same as those in Example 1.

[0086] Example 6

[0087] The difference between this embodiment and embodiment 1 is that the sputtering time in the deposition process of the transition layer is adjusted to 10 s, so that the thickness of the transition layer is 50 nm.

[0088] The rest of the preparation methods and parameters were the same as those in Example 1.

[0089] Example 7

[0090] The difference between this embodiment and embodiment 1 is that the sputtering time in the deposition process of the transition layer is adjusted to 16 s, so that the thickness of the transition layer is 80 nm.

[0091] The rest of the preparation methods and parameters were the same as those in Example 1.

[0092] Example 8

[0093] The difference between this embodiment and embodiment 1 is that the sputtering time in the deposition process of the transition layer is adjusted to 20 s, so that the thickness of the transition layer is 100 nm.

[0094] The rest of the preparation methods and parameters were the same as those in Example 1.

[0095] Example 9

[0096] The difference between this embodiment and embodiment 1 is that the sputtering time in the deposition process of the copper layer is adjusted to 65 s, so that the thickness of the copper layer is 0.5 μm.

[0097] The rest of the preparation methods and parameters were the same as those in Example 1.

[0098] Example 10

[0099] The difference between this embodiment and embodiment 1 is that the sputtering time in the deposition process of the copper layer is adjusted to 650 s, so that the thickness of the copper layer is 5 μm.

[0100] The rest of the preparation methods and parameters were the same as those in Example 1.

[0101] Embodiment 11

[0102] The difference between this embodiment and embodiment 1 is that the sputtering time in the deposition process of the copper layer is adjusted to 1300 s, so that the thickness of the copper layer is 10 μm.

[0103] The rest of the preparation methods and parameters were the same as those in Example 1.

[0104] Example 12

[0105] The difference between this embodiment and embodiment 1 is that the thickness of the commercial aluminum foil is 1 μm.

[0106] The rest of the preparation methods and parameters were the same as those in Example 1.

[0107] Embodiment 13

[0108] The difference between this embodiment and embodiment 1 is that the negative electrode conductive layer uses an electrolytic copper foil with a thickness of 1 μm, and then a transition layer is deposited on one side of the electrolytic copper foil, and then a layer of aluminum with a thickness of 0.5 μm is deposited on the surface of the transition layer by evaporation.

[0109] The rest of the preparation methods and parameters were the same as those in Example 1.

[0110] Embodiment 14

[0111] The difference between this embodiment and embodiment 1 is that the thickness of the commercial aluminum foil is 20 μm.

[0112] The rest of the preparation methods and parameters were the same as those in Example 1.

[0113] Embodiment 15

[0114] The difference between this embodiment and embodiment 1 is that the negative electrode conductive layer is a nickel layer, the negative electrode protective layer is a nickel oxide layer, the preparation method of the negative electrode conductive layer is an electroplating method, and the specific process conditions are:

[0115] An aqueous solution containing 300 g / L NiSO4·6H2O, 150 g / L NiCl2·6H2O and 52 g / L H3BO3 was used as the plating solution at 5 A / dm 2 The nickel plate is electroplated at a current density of 95 s, then cleaned to remove residual liquid on the surface, and dried at 70° C. The negative electrode protective layer is produced by in-situ oxidation during the nickel electroplating drying process.

[0116] The rest of the preparation methods and parameters were the same as those in Example 1.

[0117] Example 16

[0118] The difference between this embodiment and embodiment 1 is that the negative electrode conductive layer is a copper-nickel alloy (the mass ratio of copper to nickel is 1:1) layer, and the material of the negative electrode protective layer is copper-chromium oxide, which is prepared by magnetron sputtering, and the specific process conditions are:

[0119] Copper-nickel material (purity 99.99%, mass ratio of copper to nickel 1:1) was used as the target material, the target power was 10 kW, the argon flow rate was 80 mL / min, the chamber vacuum was 0.1 Pa, the sputtering time was 133 s, and the main roller cooling temperature was -10 °C.

[0120] The rest of the preparation methods and parameters were the same as those in Example 1.

[0121] Embodiment 17

[0122] The difference between this embodiment and embodiment 1 is that the negative electrode conductive layer is a copper foil with a thickness of 6 μm, and the positive electrode conductive layer is a carbon layer with a thickness of 1 μm. The preparation method includes:

[0123] The copper foil was placed in a magnetron sputtering machine with a graphite target (purity of 99.99%) as the target material, a target power of 3 kW, an argon flow rate of 50 mL / min, a chamber vacuum of 0.08 Pa, a sputtering time of 200 s, and a main roller temperature of 0°C during the deposition process, thereby preparing a 1 μm thick carbon layer on the surface of the copper foil.

[0124] The rest of the preparation methods and parameters were the same as those in Example 1.

[0125] Embodiment 18

[0126] The difference between this embodiment and embodiment 1 is that the bipolar current collector includes two transition layers, which are a first transition layer and a second transition layer in a direction away from the negative electrode conductive layer, and the thickness of the first transition layer and the second transition layer are both 10 nm.

[0127] The mass ratio of nickel to chromium in the nickel-chromium alloy of the first transition layer is 60:40; in the preparation method parameters, the target power is 5.2 kW and the sputtering time is 1 s.

[0128] The mass ratio of nickel to chromium in the nickel-chromium alloy of the second transition layer is 80:20; in the preparation method parameters, the target power is 5.0 kW and the sputtering time is 1 s.

[0129] During the preparation process, magnetron sputtering is used to deposit two transition layers on one surface of the aluminum foil.

[0130] The rest of the preparation methods and parameters were the same as those in Example 1.

[0131] Embodiment 19

[0132] The difference between this embodiment and embodiment 1 is that the material of the negative electrode conductive layer includes copper and chromium, and the mass fraction of chromium in the negative electrode conductive layer is 1%, that is, during the preparation process of the negative electrode conductive layer, the target material is adjusted to a copper-chromium alloy, and the mass content of chromium is 1%, and the target power is 12kW; the material of the negative electrode protective layer is copper-chromium oxide.

[0133] The rest of the preparation methods and parameters were the same as those in Example 1.

[0134] Embodiment 20

[0135] The difference between this embodiment and embodiment 1 is that the mass content of nickel in the nickel-chromium target is 5%, and the target power is 6.2 kW, so that the mass ratio of nickel to chromium in the nickel-chromium alloy of the transition layer is 5:95.

[0136] The rest of the preparation methods and parameters were the same as those in Example 1.

[0137] Embodiment 21

[0138] The difference between this embodiment and embodiment 1 is that the mass content of nickel in the nickel-chromium target is 95%, and the target power is 4.5 kW, so that the mass ratio of nickel to chromium in the nickel-chromium alloy of the transition layer is 95:5.

[0139] The rest of the preparation methods and parameters were the same as those in Example 1.

[0140] Embodiment 22

[0141] The difference between this embodiment and embodiment 1 is that the sputtering time in the deposition process of the transition layer is adjusted to 0.6 s, so that the thickness of the transition layer is 3 nm.

[0142] The rest of the preparation methods and parameters were the same as those in Example 1.

[0143] Embodiment 23

[0144] The difference between this embodiment and embodiment 1 is that the sputtering time in the deposition process of the transition layer is adjusted to 22 seconds, so that the thickness of the transition layer is 110 nm.

[0145] The rest of the preparation methods and parameters were the same as those in Example 1.

[0146] Embodiment 24

[0147] The difference between this embodiment and embodiment 1 is that the sputtering time in the deposition process of the copper layer is adjusted to 39 s, so that the thickness of the copper layer is 0.3 μm.

[0148] The rest of the preparation methods and parameters were the same as those in Example 1.

[0149] Embodiment 25

[0150] The difference between this embodiment and embodiment 1 is that the negative electrode conductive layer uses an electrolytic copper foil with a thickness of 1 μm, and then a transition layer is deposited on one side of the electrolytic copper foil, and then a layer of aluminum with a thickness of 0.3 μm is deposited on the surface of the transition layer by evaporation.

[0151] The rest of the preparation methods and parameters were the same as those in Example 1.

[0152] Embodiment 26

[0153] The difference between this embodiment and embodiment 1 is that the power frequency in the deposition process of the transition layer is adjusted to 50 kHz, the sputtering time is adjusted to 1.5 s, and the temperature of the coating main roller is adjusted to 30°C.

[0154] The rest of the preparation methods and parameters were the same as those in Example 1.

[0155] Embodiment 27

[0156] The difference between this embodiment and embodiment 1 is that the power frequency in the deposition process of the transition layer is adjusted to 5 kHz, the sputtering time is adjusted to 3.0 s, and the temperature of the coating main roller is adjusted to 5°C.

[0157] The rest of the preparation methods and parameters were the same as those in Example 1.

[0158] Comparative Example 1

[0159] The difference between this comparative example and Example 1 is that the material of the transition layer is single element nickel and the target power is 4.5 kW.

[0160] The rest of the preparation methods and parameters were the same as those in Example 1.

[0161] Comparative Example 2

[0162] The difference between this comparative example and Example 1 is that the material of the transition layer is elemental chromium and the target power is 6.5 kW.

[0163] The rest of the preparation methods and parameters were the same as those in Example 1.

[0164] Comparative Example 3

[0165] The difference between this comparative example and Example 1 is that no transition layer is provided.

[0166] The rest of the preparation methods and parameters were the same as those in Example 1.

[0167] Comparative Example 4

[0168] The difference between this embodiment and embodiment 1 is that the power frequency in the deposition process of the transition layer is adjusted to 4.5 kHz, the sputtering time is adjusted to 3.2 s, and the temperature of the coating main roller is adjusted to 5°C.

[0169] The rest of the preparation methods and parameters were the same as those in Example 1.

[0170] Comparative Example 5

[0171] The difference between this embodiment and embodiment 1 is that the power frequency in the deposition process of the transition layer is adjusted to 55 kHz, the sputtering time is adjusted to 1.2 s, and the temperature of the coating main roller is adjusted to 30°C.

[0172] The rest of the preparation methods and parameters were the same as those in Example 1.

[0173] Performance Testing

[0174] 1. The adhesion, tensile strength, elongation at break, square resistance and crystallinity of the bipolar current collectors provided in the above embodiments and comparative examples were tested. The specific testing methods are as follows:

[0175] 1) Adhesion

[0176] The complex current collector was placed in an adhesion test device and tested as follows: a layer of Permacel P-94 double-sided tape was adhered to a 1 mm thick aluminum foil, the positive electrode conductive layer of the complex current collector was adhered to the double-sided tape, and then a layer of ethylene acrylic acid copolymer film (DuPont Nurcel0903, thickness 50 μm) was covered on the negative electrode conductive layer, and then 5 N / m 2, hot pressing at 120°C for 10s, cooling to room temperature 25°C, and cutting into 150mm×15mm strips. Finally, the ethylene acrylic acid copolymer film of the sample strip is fixed to the upper fixture of the tensile machine, and the rest is fixed to the lower fixture. After fixing, the two are peeled at an angle of 180° and a speed of 100mm / min to test the peeling force. The peeling force obtained is the bonding force between the negative electrode conductive layer and the positive electrode conductive layer in the multipolar current collector.

[0177] 2) Tensile strength and elongation at break

[0178] Refer to national standard GB / T 1040.3-2006.

[0179] 3) Square resistance

[0180] The bipolar current collector sample is placed on a sample stage, and the square resistance of two opposite surfaces of the sample is tested respectively using a four-probe square resistance meter.

[0181] 4) Crystallinity

[0182] The crystallinity of the transition layer in the bipolar current collector is tested by X-ray diffraction. The finished bipolar current collector is taken, and the copper layer is first thinned to a thickness of 0 (thinning methods such as focused ion beam can be used), and then the treated sample is placed in an X-ray diffractometer and scanned in the range of 5-90 degrees at a rate of 2° / min to obtain a diffraction curve. The crystallinity can be calculated by combining the diffraction curve and using the following formula:

[0183] Xc=Ic / (Ic+Ia)×100%

[0184] Wherein, Ic is the diffraction integrated intensity of the crystalline part, Ia is the diffraction integrated intensity of the amorphous part, and Xc is the crystallinity.

[0185] The test results are shown in Table 1.

[0186] Table 1

[0187]

[0188]

[0189]

[0190] 2. A solid-state lithium battery is prepared based on the bipolar current collector provided in the above embodiment and comparative example, and the specific steps include:

[0191] ① Coating electrode materials on the positive conductive layer side, the electrode materials include LiNi 0.8 Co 0.1 Mn 0.1O2 (NCM811), conductive carbon black Super P, PVDF 5130 and carbon nanotubes CNT, with a mass ratio of 96:1.8:1.7:0.5.

[0192] ② Coating the electrode material on the negative electrode conductive layer side, the electrode material includes graphite, conductive carbon black SuperP, carbon nanotubes and CMC, with a mass ratio of 96:3.0:0.6:0.4.

[0193] ③ Use Li6PS5Cl as the solid electrolyte and assemble it into a soft-pack battery with a capacity of 3Ah according to the assembly process of bipolar solid-state batteries.

[0194] The above-assembled soft-pack battery was subjected to a cycle performance test, and the test conditions were as follows: charge and discharge at a constant current constant voltage (CCCV) rate of 1C, and discharge at a constant current (CC) rate of 1C, and the charge and discharge cycle was repeated 2000 times. The battery capacity retention rate after 2000 cycles of charge and discharge was recorded, that is, the battery capacity after 2000 cycles of charge and discharge / the initial capacity of the battery × 100%.

[0195] The test results are shown in Table 2.

[0196] Table 2

[0197]

[0198]

[0199]

[0200] analyze:

[0201] As can be seen from Tables 1 and 2, the present invention adds a transition layer comprising a nickel-chromium alloy, which can not only improve the bonding force between the negative electrode conductive layer and the positive electrode conductive layer, thereby improving the stability of the interface and ensuring that the complex current collector has good structural stability, but also promote the application stability of the complex current collector in the bipolar battery and improve the cycle performance of the bipolar battery.

[0202] It can be seen from Examples 1-4, Example 20 and Example 21 that as the mass proportion of nickel in the transition layer continues to increase, the bonding force between the negative electrode conductive layer and the positive electrode conductive layer in the prepared multi-electrode current collector first increases and then decreases. This is because as the nickel content increases, the force between the transition layer and the conductive layer first increases and then decreases. In addition, the corresponding tensile strength and elongation at break also show a trend of first increasing and then decreasing, which is due to the change in bonding force. The corresponding square resistance changes little, because the square resistance mainly depends on the material and thickness of the positive and negative electrode conductive layers. In addition, if the nickel content in the transition layer is too low, the cycle performance of the battery deteriorates; if the nickel content in the transition layer is too high, the cycle performance of the battery deteriorates.

[0203] It can be seen from Example 1, Example 5-8, Example 22 and Example 23 that as the thickness of the transition layer continues to increase, the bonding force between the negative electrode conductive layer and the positive electrode conductive layer in the multi-electrode current collector shows an increasing trend. Due to the increase in the thickness of the transition layer, the uniformity of the transition layer first increases and then remains unchanged, so that the force with the conductive layer first increases and then remains unchanged, so the corresponding tensile strength and elongation at break also show the same change trend. The corresponding square resistance changes less, because the square resistance mainly depends on the material and thickness of the positive and negative electrode conductive layers. When the thickness exceeds 100nm, the mechanical properties of the prepared multi-electrode current collector no longer change. In addition, if the thickness of the transition layer is too small, the cycle performance of the battery is poor; if the thickness of the transition layer is too large, the cycle performance of the battery is improved by a small margin. Therefore, the thickness of the transition layer is preferably 10-100nm.

[0204] It can be seen from Example 1, Examples 9-11 and Example 24 that as the thickness of the negative electrode conductive layer increases, the square resistance of the complex current collector decreases, the conductivity increases, the corresponding tensile strength increases, the elongation at break decreases, and the corresponding bonding force remains unchanged. This is because the bonding force mainly depends on the properties of the transition layer. Considering the conductivity, the thickness of the negative electrode conductive layer should be ≥0.5μm. Further considering the problem of reduced battery energy density caused by increased thickness of the conductive layer, the thickness of the negative electrode conductive layer is preferably in the range of 1-10μm.

[0205] It can be seen from Example 1, Example 12-14 and Example 25 that as the thickness of the positive electrode conductive layer increases, the square resistance of the complex current collector decreases, the conductivity increases, the corresponding tensile strength increases, the elongation at break decreases, and the corresponding bonding force remains unchanged. This is because the bonding force mainly depends on the properties of the transition layer. Considering the conductivity, the thickness of the positive electrode conductive layer should be ≥0.5μm. Further considering the problem of reduced battery energy density caused by increased thickness of the conductive layer, the thickness of the positive electrode conductive layer is preferably in the range of 1-10μm.

[0206] It can be seen from Example 1 and Examples 15-17 that good effects can also be achieved by replacing the material of the positive electrode conductive layer or the negative electrode conductive layer with other materials.

[0207] It can be seen from Example 1 and Examples 18-19 that two transition layers are used, and the mass ratio of nickel to chromium in the nickel-chromium alloy of the first transition layer is regulated to be 60:40, and the mass ratio of nickel to chromium in the nickel-chromium alloy of the second transition layer is 80:20, so that the nickel content in the two transition layers presents a gradient change, which helps to reduce the interface resistance between the transition layer and the conductive layer, and improve the structural stability of the transition layer, thereby improving the cycle performance of the battery. If the material of the negative electrode conductive layer includes copper and chromium, the combination of the two helps to improve the mechanical properties and corrosion resistance of the complex current collector, thereby improving the cycle performance of the assembled battery.

[0208] It can be seen from Example 1, Examples 26-27 and Comparative Examples 4-5 that as the frequency of the magnetron sputtering power supply increases, the crystallinity increases, and the battery cycle performance first increases and then decreases. This is because the transition layer has too high crystallinity, which makes the transition layer brittle and prone to breakage during the rolling process of the prepared pole piece, resulting in defects, resulting in poor material stability, thereby causing poor battery cycle performance.

[0209] It can be seen from Example 1 and Comparative Examples 1-2 that if the material of the transition layer is elemental nickel or elemental chromium, it is not conducive to the close bonding between the positive and negative conductive layers, resulting in poor structural stability of the bipolar current collector, and further causing poor cycle performance of the assembled battery.

[0210] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A bipolar current collector, characterized in that: The bipolar current collector comprises a negative electrode conductive layer and a positive electrode conductive layer which are stacked, and at least one transition layer is stacked between the negative electrode conductive layer and the positive electrode conductive layer; The material of the transition layer is nickel-chromium alloy, and the crystallinity of the nickel-chromium alloy is 5-80%.

2. The bipolar current collector according to claim 1, characterized in that: The transition layer is a non-porous structure.

3. The bipolar current collector according to claim 1 or 2, characterized in that: In the nickel-chromium alloy, the mass percentage of nickel is 10-90%; Preferably, the nickel-chromium alloy has a crystallinity of 20-60%; Preferably, the single layer thickness of the transition layer is 5-100 nm, preferably 10-100 nm.

4. The bipolar current collector according to any one of claims 1 to 3, characterized in that: At least two transition layers are stacked between the negative electrode conductive layer and the positive electrode conductive layer, and the mass content of nickel in the at least two transition layers increases gradually in a direction away from the negative electrode conductive layer or the positive electrode conductive layer; Preferably, the total thickness of the at least two transition layers is 10-100 nm.

5. The bipolar current collector according to any one of claims 1 to 4, characterized in that: The thickness of the negative electrode conductive layer is ≥0.1 μm, preferably 1-10 μm; Preferably, the thickness of the positive electrode conductive layer is ≥0.5 μm, preferably 1-10 μm; Preferably, the total thickness of the negative electrode conductive layer and the positive electrode conductive layer is ≥2 μm; Preferably, the material of the negative electrode conductive layer includes any one or a combination of at least two of copper, nickel, titanium, carbon, gold or silver, preferably any one or a combination of at least two of copper, nickel or carbon; Preferably, the negative electrode conductive layer further includes a doping element; Preferably, the doping element includes any one or a combination of at least two of tungsten, manganese, iron, chromium, cobalt, zirconium, tantalum, niobium or tin; Preferably, the mass fraction of the doping element in the negative electrode conductive layer is 0.01-10%; Preferably, the material of the positive electrode conductive layer includes any one of aluminum, carbon, gold or silver, or a combination of at least two thereof, preferably aluminum and / or carbon.

6. The bipolar current collector according to any one of claims 1 to 5, characterized in that: A protective layer is provided on the surface of the negative electrode conductive layer and / or the positive electrode conductive layer away from the transition layer; Preferably, the thickness of the protective layer is 5-100 nm, preferably 10-80 nm; Preferably, the material of the protective layer includes any one of a metal element, a carbon material, an alloy or an oxide, or a combination of at least two of them.

7. A method for preparing a bipolar current collector according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: Providing a positive electrode conductive layer, and then compounding at least one transition layer and a negative electrode conductive layer in sequence on one side surface of the positive electrode conductive layer to obtain the bipolar current collector; Alternatively, a negative electrode conductive layer is provided, and then at least one transition layer and a positive electrode conductive layer are compounded in sequence on one side surface of the negative electrode conductive layer to obtain the bipolar current collector.

8. The preparation method according to claim 7, characterized in that: The composite method of the at least one transition layer comprises at least one method selected from the group consisting of mechanical rolling, bonding, vapor deposition, chemical plating or electroplating; Preferably, the vapor deposition method includes magnetron sputtering and / or vacuum evaporation; Preferably, the composite method of the at least one transition layer is magnetron sputtering, and the specific parameters independently include: The target material is a nickel-chromium target with a nickel mass content of 10-90%, the power supply is a pulsed DC power supply, the power frequency is 5-50kHz, the target power is 2-20kW, the gas flow rate is 30-500mL / min, the chamber vacuum is ≤0.1Pa, and the coating main roller cooling temperature is 5-30℃; Preferably, the preparation methods of the positive electrode conductive layer and the negative electrode conductive layer are independently any one of physical vapor deposition, chemical vapor deposition, rolling or coating-drying methods, or a combination of at least two thereof.

9. Use of the bipolar current collector according to any one of claims 1 to 6 in the fields of electromagnetic shielding, flexible circuits and printed circuit boards.

10. A battery, characterized in that: The pole piece in the battery comprises the bipolar current collector as described in any one of claims 1-6.

Citation Information

Patent Citations

  • Cermet covering material, alloy powder for manufacturing cermet covering material, and method for manufacturing cermet covering material

    CN104271785A

  • Antibacterial antifouling metal film pad

    CN110920164A

  • Composite current collector and preparation method and application thereof

    CN116504990A

  • Negative current collector and preparation method thereof, negative pole piece and battery

    CN118522899A

  • Carrier-provided copper foil, printed wiring board, printed circuit board, copper-clad laminate and method of producing printed wiring board

    JP2014172183A

Cited By

  • Carbon composite current collector for laminated solid-state battery, preparation method of carbon composite current collector and laminated solid-state battery

    CN121416520A

  • Bipolar current collector and manufacturing method therefor, battery, and application

    WO2026108798A1